New Mindset, New Results - Johnson, Kerry (Ascent Audio, 2019)
Your Mindset impacts everything you think, say, and do. Your Mindset creates hope and hopelessness, success and failure. It is the software your brain uses to create attitude, experience, and achievement. It is also the filter that builds behavior. Your mindset causes you to blame others for failure or learn from experience. Your Mindset helps you make sense of everything that happens. It is the prism through which you experience life. Research has shown those with a Results Focused, Growth Mindset make more money and are happier than those who choose to limit themselves. Those with a fixed mindset make excuses for setbacks instead of learning from mistakes. Your Mindset will help you build self-confidence and self-discipline. It will help you overcome any obstacle and any problem. All you need is a new Results Focused Mindset.